O circo é bem-sucedido mesmo se falta o pão: avaliação do Veículo Leve Sobre Trilhos (VLT) na percepção da população atingida: Comunidade Trilha do Senhor - Menezes, Lidiana Barreto de Sousa (2013)
Brazil is going to host 2014 FIFA World Cup, and Fortaleza was selected as one of the host cities, which is going to go through several changes in order to be adapted for the event. In terms of Urban Mobility, it is being carried out a Light Rail Project which is going to cross 22 neighborhoods in 13 kilometers after its conclusion, impacting on about five thousand houses. The way this project is being carried out is the focus of this study, having as its general purpose to evaluate the process of the implementation of the Light Rail (LR) by the inhabitants’ point of view from a community affected by the removal, and its influences on the urban space of Fortaleza. The research is based mainly on the action taken over social actors, members of the community affected by the Works, in relation to its physical, social and political aspects. There was an analisys carried out on how Ceará Government State led the process of LR implementation regarding to the existent communities along the way of the works of the project, the process of vacancy/expropriation of those areas, as well as the identification of the Government’s adopted measures, in the urban context of the city in order to get to the houses that are going to be demolished in the expropriation process.